The Effect of Social Capital on Farmer Welfare - Prettyziana Sekar Arum; Jabal Tarik Ibrahim; Ary Bakhtiar (Universitas Muhammadiyah Malang, 2023)
The agricultural sector significantly contributes to the national income, warranting focused attention for its continuous development and enhanced productivity to positively effect farmer welfare. Farmer groups, pivotal in harnessing the potential and knowledge of farmers in agriculture, play a crucial role in fostering competitive productivity. The establishment of farmer interactions is facilitated by the presence of social capital within farming communities, underscoring its vital role in realizing farmer welfare. This study seeks to analyze the effect of social capital variables on the welfare of farmers within Gapoktan Agro Mandiri, situated in Selur, Ngrayun, Ponorogo, Indonesia. Employing quantitative methods and utilizing the SmartPLS analysis tool, the research gathered data from 84 respondents, determined through calculations using the Slovin formula. The findings reveal a substantial 72.4% influence of social capital on farmers' welfare within GAPOKTAN Agro Mandiri. This underscores that components of social capital, including trust, networks, and social norms, collectively contribute positively to the welfare of farmers. The demonstrated significance of social capital in this context emphasizes its pivotal role in supporting farmer development and enhancing welfare within the specified region.